Optimal Distribution Network Reconfiguration with Distributed Generation using a Genetic Algorithm - Peñaloza, John (2019)
This paper presents the develop of a computational tool for solve the distribution network reconfiguration problem considering the power losses minimization and distributed generation. The proposed tool satisfies the operational constraints of systems, e.g., voltage limits in nodes and the current capacity of lines. The use of a MINLP and a Genetic Algorithm guarantees convergence to good quality solutions. This is a searching adaptive method - based on natural selection and natural genetic. It improves the solutions in combinatorial problems, in each iteration through their operators (selection, crossover and mutation). 14-Bus, 33-Bus and 69-bus test systems and 880-Bus real system were employed to show the effectiveness and satisfactory results of the proposed tool.